STUDENTS’ PERCEPTIONS OF TECHNOLOGY INTEGRATION AND MEDIA USE IN LEARNING ACTIVITIES: A MIXED-METHODS APPROACH - Nur Kamilasari; Sunarti; Ibrahim (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study investigates university students’ perceptions of technology integration and media use in English language learning using a mixed-methods approach. Quantitative data were collected from 432 students via a Likert-scale questionnaire and analyzed through descriptive and inferential statistics, including Mann-Whitney U and Kruskal-Wallis H tests. The findings showed a generally positive perception (M = 48.30, SD = 5.81), with no significant differences based on gender (p = .163), but a significant variance based on semester level (p = .026), indicating improved perception with higher academic exposure. Qualitative data from interviews with selected students revealed five central themes: ease of access, technical challenges, platform overload, preference for blended learning, and the influence of prior digital experience. Students favored media such as Kahoot, videos, and animations for their engaging features, although their long-term impact on learning was questioned. Participants with earlier exposure to digital tools adapted more confidently, while others initially struggled. Both statistical and thematic analyses highlight the importance of pedagogical alignment, infrastructure stability, and gradual digital familiarization. The study underscores that technology and media can enhance English learning when meaningfully integrated into instruction and supported by institutional strategies.